Residence Heads as Intentional Role‘s Players in Promoting Student Success (Journal of Student Affairs in Africa, 2021)
Research evidence suggests that approaches to promote student success in higher education are becoming more holistic and integrated in nature. This implies that not only classrooms and laboratories, but also residences, as informal out-of-class learning environments, can potentially contribute significantly to promoting student success. The research question we sought to answer is: what is the preferred role and skill sets of residence heads that will enable them to promote student success? In order to answer this question, the study proposes a student success framework with five levels, and the role of the future residence head is explicated in terms of this framework. The findings of the study are significant as they suggest a practical skill set, underpinned by sound theory, for residence heads to contribute to student success.
Keywords: blended higher education roles; educational mindset; residence heads; residence heads’ skill sets; student affairs; student success levels